Pancreatic lipase‐related protein 2 is responsible for the increased hepatic retinyl ester hydrolase activity in vitamin A‐deficient mice. (28th June 2019) - Gao, Yan; Lu, Weiling; Sun, Qi; Yang, Xiao; Liu, Junhao; Ge, Wenhao; Yang, Yunxia; Zhao, Yang; Xu, Xi; Zhang, Jianfa
Abstract : The formation and hydrolysis of hepatic retinyl esters (RE) is a key process in maintaining serum retinol homeostasis. During vitamin A deficiency, the activity of RE hydrolases (REH) in liver increases to cope with the reduced dietary vitamin A intake. However, it remains unclear which REH is the main enzyme responsible for RE hydrolysis in the liver under physiological conditions. Our previous studies have shown that pancreatic lipase‐related protein 2 (PLRP2) is conditionally expressed in the liver and may be involved in the hydrolysis of hepatic RE. In the current study, we generated Plrp2 −/− mice using transcription activator‐like effector nuclease technology to investigate the role of PLRP2 in the metabolism of hepatic RE. Compared with the mice fed normal diet, the hepatic REH activity of wild‐type (WT) mice fed vitamin A‐deficient diet (VAD) increased significantly, while this activity did not increase in Plrp2 −/− mice fed VAD. Plrp2 −/− mice showed higher residual RE content in liver and lower serum retinol level, compared with WT mice fed VAD. Hepatic metabolic profiling from 1 H NMR‐based metabolomics suggested that Plrp2 −/− mice were more sensitive to VAD. Docking analysis and enzyme activity assay revealed that retinyl palmitate was the substrate with higher affinity for PLRP2. Our results indicate that Plrp2 can be activated in the liver and is responsible for the increased REH activity in the liver of mice fed VAD. Abstract : It is known that hepatic retinyl ester hydrolase (REH) activity increases under vitamin A‐deficient conditions. However, it is not known which REH enzyme is responsible for this activity in the liver in physiological conditions. In the present study, we demonstrate that pancreatic lipase‐related protein 2 activates and participates in the mobilization of retinyl esters in the liver of mice under vitamin A‐deficient status.